Expert recommendations for pancreatitis/pancreatic necrosis treatment after L-asparaginase in children with acute lymphoblastic leukemia - T. T. Valiev; E. V. Kumirova; V. M. Rozinov; T. R. Panferova; I. N. Khvorostov; K. L. Kondratchik; O. Yu. Fuks; P. A. Kerimov; N. V. Matinyan; A. V. Belyaeva; A. M. Efremenkov; A. A. Bystrova; et al. (Онкогематология)
L-asparaginase is one of the most effective drugs in pediatric and adult acute lymphoblastic leukemia treatment. But drug side effects are an important problem. pancreatitis and pancreatic necrosis are not common (2–18 %) complication, but high chance of severe disease with fatal outcome make to bring in careful attention of pediatric oncologists-hematologists, surgeons, intensivists, radiologists. Recognizing multidisciplinary importance of this problem, at June 21st, 2023 at Morozov Children’s Clinical hospital a Round table on pancreatitis/pancreatic necrosis after L-asparaginase use was organized. This article presents expert recommendations from federal and regional clinics in diagnosis and treatment of such severe complication.